ANALISIS PUISI PENDEKATAN STRUKTURAL - Nya Revi Rendika (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
Abstract This study aims to identify and recognize in detail the poems by Chairil Anwar and Amir Hamzah and then analyzed with a structural approach. This study uses a qualitative research method library research type. Data analysis was carried out by analyzing the content contained in the structure of the poem with existing theories. The results showed that the two poems presented contained various typography with good use of diction. The conclusion in each poem gives a variety of messages, where Chairil Anwar's poem mandates never to second-guess someone who loves sincerely and selflessly. Because when sincerity is tarnished then someone will be hurt. And the mandate in Amir Hamzah's poetry is that if there is someone who loves us with all their heart, then we should never try to find another love because of a new love, because the new one is not necessarily good.